The Readiness of Biology Laboratories to Support Practical Work in State High Schools throughout Tegal Regency - Rizqiyati, Ni'mah; Anggraito, Yustinus Ulung; Ridlo, Saiful (FMIPA UNNES, 2018)
This study aimed to analyze the readiness of biology laboratories to support practical work in State High Schools throughout Tegal Regency. The readiness refers to the availability of all things that can support practical activities including the readiness of infrastructure facilities and laboratory management. This study used quantitative descriptive research design. The population in this study is all independent biology laboratories in State High Schools throughout Tegal Regency that used for practical works. The sampling technique used is saturation sampling. This study has been done at biology laboratory of SMA Negeri 1 Bojong, SMA Negeri 1 Kramat, SMA Negeri 1 Warureja, SMA Negeri 1 Balapulang, SMA Negeri 1 Pangkah, SMA Negeri 1 Slawi, SMA Negeri 2 Slawi, SMA Negeri 3 Slawi, dan SMA Negeri 1 Pagerbarang. The data were obtained using the observation method, questionnaire, and interview with reference to Permendiknas Number 24 Year 2007, Permendiknas Number 26 Year 2008, and Permendikbud Number 24 Year 2016. Further, the data were analyzed using descriptive statistics. The result of the study shows that the readiness of infrastructure facilities and management successively scored 58.5% and 62.8% which is belonged to sufficient criteria. The conclusion of this study is the biology laboratories in State High Schools throughout Tegal Regency is ready enough to support biological practical work with an average readiness of 60.52%.